Tuning Surface Morphology of Fluorescent Hydrogels Using a Vortex Fluidic Device - Javad Tavakoli (Molecules, 2020)
In recent decades, microfluidic techniques have been extensively used to advance hydrogel design and control the architectural features on the micro- and nanoscale. The major challenges with the microfluidic approach are clogging and limited architectural features: notably, the creation of the sphere, core-shell, and fibers. Implementation of batch production is almost impossible with the relatively lengthy time of production, which is another disadvantage. This minireview aims to introduce a new microfluidic platform, a vortex fluidic device (VFD), for one-step fabrication of hydrogels with different architectural features and properties. The application of a VFD in the fabrication of physically crosslinked hydrogels with different surface morphologies, the creation of fluorescent hydrogels with excellent photostability and fluorescence properties, and tuning of the structure–property relationship in hydrogels are discussed. We conceive, on the basis of this minireview, that future studies will provide new opportunities to develop hydrogel nanocomposites with superior properties for different biomedical and engineering applications.